Spectral Reallocation in Lightpaths Encompassing the Most Fragmented Link of Elastic Optical Networks - Favero, Ricardo Vicente; Bonani, Luiz Henrique; Francisco Abbade, Marcelo Luis [UNESP]; IEEE (Ieee, 2016)
Dynamic allocation and release of lightpaths cause spectral fragmentation and degrade the bandwidth occupation in elastic optical networks (EON). Spectral reallocation and defragmentation strategies are key issues to minimize this problem and should be carefully chosen to simplify network management and to avoid excessive use of hardware. In this paper, we investigate the application of three different routing and spectral assignment (RSA) algorithms to reallocate EON traffic in situations where new requested connections may be potentially blocked. A fragmentation index is computed for all EON links and only those lightpaths that encompass the most fragmented link are prone to reallocation. Computer simulations suggest the choice of an appropriate RSA may reduce the relative blocking probability by similar to 18% for a traffic load of 70 E. We also investigate the number of reallocations that actually lead to spectral defragmentation.